Validation of Coding Algorithms for the Identification of Patients with Primary Biliary Cirrhosis Using Administrative Data - Robert P Myers; Abdel Aziz M Shaheen; Andrew Fong; Alex F Wan; Mark G Swain; Robert J Hilsden; Lloyd Sutherland; Hude Quan (Canadian Journal of Gastroenterology)
BACKGROUND: Large-scale epidemiological studies of primary biliary cirrhosis (PBC) have been hindered by difficulties in case ascertainment.